Schadensidentifikation mit modalen Parametern: Anwendung auf extern vorgespannte Hohlkastenbrücken - Haag, Björn (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2016)
With a focus on the monitoring of concrete bridges, this study evaluates 19 different methods under realistic constraints. Then, the detailed numerical model of an unbonded post-tensioned box-girder bridge is created. There, nonlinear material laws, which have been validated by laboratory tests, are applied. Combining six different methods, the increase in cracking as a consequence of either the settlement of the pier or the decrease in the tension force can be assessed and localized.